Advaita Vedānta and the Poetic Exploration of Transcendence in W.B. Yeats’ Poetry (Literary Voice, 2024)
This paper delves into the intricate interplay between Vedānta philosophy and the pursuit of universality in select poems by the esteemed Irish poet, W.B. Yeats. Drawing upon the philosophical tenets of Vedānta, which emphasize the inherent unity of all existence, this study examines how Yeats, a poet deeply influenced by the Eastern thought, grapples with and explores these profound ideas in his poetic oeuvre. Through an in-depth analysis of select poems, I aim to unravel the nuanced ways Yeats engages with Vedānta philosophy, seeking to transcend cultural and temporal boundaries in his quest for a universal poetic vision. Furthermore, the paper endeavours to elucidate why it is imperative to comprehend World Literature through Indic perspectives, challenging the foreign origins of the term. The argument posits the need to develop a theoretical framework rooted in the Indian viewpoint to comprehend literature from diverse global traditions.
Keywords: Vedānta philosophy, W.B. Yeats, mysticism, universality, non-dualism, Eastern thought, poetry, Advaita, self-realization.